OPHTHALMOLOGICAL AND NEUROLOGICAL MANIFESTATIONS OF A DOG WITH INTRACRANIAL ANAPLASTIC EPENDYMOMA. CASE REPORT - FERRAZ, C.; TORRES NETO, R.; ROMALDINI, A.; CIRIO, S. M.; DEL FAVA, C. (Ars Veterinaria, 2021)
The objective is to report ependymoma associated with uveitis in a four-month-old male boxer crossbreed. The dog initially presented in both eyes conjunctival hyperemia, blepharospasm, projection of the nictitating membrane, and photophobia, characteristic of uveitis.Traumatic uveitis was rejected. Six days after onset of ophthalmic symptoms, vomiting, incoordination, and behavior changes occurred. Neurological symptoms and eyebrow contraction suggesting head pain and brain injury were investigated by computed tomography (CT) nine days after, when the dog showed spasms of the limbs and neck followed by respiratory arrest with reversal and stabilization. The scans revealed extensive amorphic neoformation in the diencephalon, midbrain, and within the right lateral ventricle, along with sinistral displacement of the cerebral sickle. The animal was euthanized, and necropsy of the head revealed hydrocephalus and an intracerebral tumor mass consistent with the CT imaging. Histopathological evaluation by hematoxylin and eosin staining revealed tissue alterations in several CNS segments, showing several pseudorosettes in the neuropil, mitosis, and a high degree of cell atypia, indicating ependymoma.Inflammatory, hemorrhagic, and necrotic tissue lesions were observed in the brainstem and cerebellum due to compression by tumor tissue and hydrocephalus. The neoplasia was phenotyped by Immunohistochemistry (IHC), and tested positive for the tumoral markers vimentin and glial fibrillary acid protein, confirming intracranial anaplastic ependymoma. Behavior changes and neurological signs resulted from vascular, inflammatory, and degenerative processes in the neuropil caused by neoplasm compression and invasion of brain tissue. Although dogs with ependymoma often present with neurological disease,in the present case, blepharospasm was the first symptom noticed by the owner, and it persisted until euthanasia. According to the literature, and confirmed in the evolution of the current case, the symptoms are related to tumor location and extent and to secondary lesions due to tumor expansion. Clinical symptomatology and complementary laboratory testing, CT, necropsy, histology, and IHC characterized ependymoma, a rare condition in young dogs.